ONLINE REVIEW AND RATING ON CONSUMER PURCHASE INTENTION: THE MODERATING ROLE OF RELIGIOSITY - Nurillah, Shinta Lintang; Aini, Zahriya Nurul; Timur, Yan Putra; Widiastuti, Tika (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: The rapid development of technology requires business people to adapt, especially in consumer decision-making. This study aims to analyze the effect of online customer reviews and online customer ratings on consumer purchase intentions. Religiosity is the moderating variable in this study. Methods The research method used is quantitative, with PLS-SEM as the evaluation model. Respondents used Muslim, gender male, and female, and were aged 17 years and over, totaling 101 respondents. Where the data was taken by providing an online questionnaire spread on Java Island from April until June 2022. Results: The results showed that online customer reviews did not affect consumers' purchase intentions. On the other hand, online customer ratings influence consumers' purchase intentions. In the moderating variable, religiosity does not have a moderating effect between the dependent and independent variables. Conclusion and suggestion: The rapid development of technology today presents many online platforms. The study's results stated that the Customer Online Review variable did not affect purchase intentions, while the customer online rating variable influenced purchase intention. The researchers advise Muslim fashion business actors who use the media marketplace as a means to sell their products to improve product quality and establish relationships with consumers so that consumers can make repeat purchases. The strategy can be used in developing a Customer Relationship Management (CRM) team.